E-Learning enhancing student’s intelligent and critical thinking - Ahmad Dahlan, Abdul Rahman; Md., Amanullah; Adnan, Muhammad (Research Publish Journals, 2015)
Education is an essential process for every human being especially students. However, students need to be more concerned with their Intelligent Quotient (IQ) and their critical thinking’s skill. This paper intends to propose a conceptual solution that provides an E-learning development of students focusing on IQ and critical thinking knowledge. The paper is based on literature review, real world observations and adopting business model canvas (BMC) framework in building a conceptual solution for learning development of human talent to enhance students’ intelligent and critical thinking. The findings of this paper shows that cyber world, that use the creativity of ICT and Internet, has been widely used around the world by entrepreneurs to build businesses based on sound human values and principles that takes into account the numerous benefits and virtues offered to the people, planet, and profits.